PENGENALAN HURUF HIJAIYAH MELALUI PENGGUNAAN MEDIA AUDIO VISUAL DI TK ANAK BANGSA LOMBOK TENGAH - Rachman, Sry Anita; Muhibbin, Muhibbin; Wathan, Hizbul (INSANTA : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
Community service (PKM) is something that must be carried out by lecturers. This PKM activity aims to introduce hijaiyah letters in the Anak Bangsa Kindergarten in Central through the use of audio visual media. The implementation of this service is carried out by providing training involving class teachers and TPQ teachers. The research subjects were 16 children from group B of the Anak Bangsa Kindergarten in Central Lombok. Data collection techniques are carried out by means of observation and documentation. The data analysis technique used is qualitative descriptive data analysis. From the PKM activities carried out, it was found that the ability to recognize hijaiyah letters had developed very well. The results of this activity show that using audio-visual media can improve the ability to recognize group B hijaiyah letters in the Anak Bangsa Kindergarten in Central Lombok.